Pemberdayaan Masyarakat Melalui Kebun Gizi Untuk Meningkatkan Ketahanan Pangan - Sintawati, Naila; Anggraeni, Dewi (J-ADIMAS (Jurnal Pengabdian Kepada Masyarakat), 2024)
Community empowerment through nutrition gardens is one of the strategic efforts to improve local food security in Rowolaku Village, Kajen District, Pekalongan Regency. The village is dominated by people who work as farmers, but access to nutritious food is still a challenge. The nutrition garden program initiated by KKN UIN K.H. Abdurrahman Wahid Pekalongan students aims to empower the community, especially PKK mothers, to create healthy food sources and prevent stunting. This community service method uses a participatory approach, in practice implemented in three stages: socialization to the community, preparation, and implementation of the nutrition garden, as well as mentoring and evaluation. PKK women play an important role in farming activities, from preparing planting media and maintenance to harvesting, with support from facilitators. The results of this program are expected to strengthen food security, increase awareness of the importance of a healthy diet, and positively contribute to the health and welfare of the Rowolaku Village community.